Predictors of Falls in a Multiethnic Population of Older Rural Adults With Diabetes - Quandt, Sara A. (2006)
BACKGROUND: Falls are a recognized danger for older adults with diabetes. Persons in rural communities with diabetes may face additional risks from falling due to environmental and activity differences. METHODS: Data were obtained in a cross-sectional survey of a stratified random sample of 691 community-dwelling adults (42.7% white, 31.4% African American, and 25.9% Native American) at least 65 years old with two or more Medicare claims for diabetes in 1998–2000, living in two rural counties in North Carolina. Falls data were self-reported for the previous year. Demographic data, foot-related symptoms, diabetes medications, and other health characteristics were reported. RESULTS: Three hundred two persons (43.7%) reported falling at least once, including 171 (26.2%) who experienced two or more (frequent) falls. Frequent fallers were more likely to be male (odds ratio [OR] = 1.76; 95% confidence interval [CI] = 1.17, 2.66), report tingling or numbness in feet (OR = 1.75; 95% CI = 1.13, 2.70), have had a stroke (OR = 1.81; 95% CI = 1.19, 2.76), have longer duration of diabetes (OR = 1.21; 95% CI = 1.00, 1.47), have lower physical functioning (OR = 0.97; 95% CI = 0.96, 0.99) and mobility (OR = 0.89; 95% CI = 0.82, 0.96), and take a greater number of prescription medications (OR = 1.07; 95% CI = 1.01, 1.13). CONCLUSIONS: For rural older adults with diabetes, falls history should be screened to identify those at risk. Further research should investigate unique environmental factors contributing to falls for rural elderly persons.